Visual Essay: Anthropology and Contemporary Art: Parody and Stereotypes in the Work of Sandow Birk - Xavier Andrade (Íconos)
Visual essay "Anthropology and Contemporary Art: Parody and Stereotypes in the Work of Sandow Birk"